DEVELOPMENT OF AGRICULTURE AND INCREASE ITS COMPETITIVENESS (British Journal of Global Ecology and Sustainable Development, 2023)
This article delves into the multifaceted strategies essential for propelling the development of agriculture and augmenting its competitiveness on the global stage. Recognizing agriculture as the backbone of economies, we explore technological advancements, sustainable practices, market integration, and policy reforms as integral components to ensure the sustained growth and resilience of this critical sector.